Young adult poetry : a survey and theme guide - Schwedt, Rachel E., 1944- (Greenwood Press, 2002)
This resource features an annotated bibliography of 198 poetry volumes and a thematic guide to over 6000 individual poems. Works span the reading levels from sixth to twelfth grade and range in style.